Silicone resin composition

A methyl silicone resin blended with magnesium fluoride particles addresses the challenge of maintaining transparency and thermal conductivity at 200°C, optimizing heat dissipation and lighting efficiency in light emitting diodes.

JP7599316B2Active Publication Date: 2024-12-13TOKUYAMA CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020197868
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-30
Publication Date
2024-12-13
Estimated Expiration
2040-11-30

AI Technical Summary

Technical Problem

Existing silicone resin compositions fail to maintain high transparency and thermal conductivity at the operating temperature of light emitting diodes (around 200°C), which is essential for efficient light utilization and heat dissipation.

Method used

A silicone resin composition comprising a methyl silicone resin with 90% or more volume of magnesium fluoride particles having a volume average particle size of 1 to 20 μm is blended to achieve high heat resistance, thermal conductivity, and transparency at 200°C.

Benefits of technology

The composition provides high transparency and thermal conductivity, enabling efficient heat dissipation and light utilization by acting as an adhesive between a light emitting diode element and a reflector, enhancing lighting efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599316000001
    Figure 0007599316000001
  • Figure 0007599316000002
    Figure 0007599316000002
Patent Text Reader

Abstract

To provide a silicone resin composition which is usable at about 200°C that is a temperature during operation of a light-emitting diode element, and can exhibit high transparency at such a using temperature.SOLUTION: A silicone resin composition is composed of a methyl-based silicone resin, and an inorganic filler that contains 90 vol.% or more of magnesium fluoride and has a volume average particle diameter of 1-20 μm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a novel silicone resin composition. [Background technology]

[0002] Composite materials in which thermally conductive fillers are mixed with resins such as epoxy resins and silicone resins are widely used as heat dissipation materials for dissipating heat from heat sources such as semiconductor elements. Among the resins used as the matrix material for these heat dissipation materials, silicone resins are widely used due to their high heat resistance and light resistance.

[0003] In addition to heat dissipation and heat resistance, silicone resin compositions used as such heat dissipation materials may require transparency as a necessary property. For example, in a light-emitting diode, a reflector is disposed around the light-emitting diode element, and light emitted from the light-emitting diode element is reflected by the reflector and collected. Here, the light-emitting diode element is bonded to a part of the reflector by an adhesive. If the adhesive is opaque, the light emitted from the adhesive surface of the light-emitting diode element cannot reach the reflector, and no light is collected. On the other hand, if the adhesive can be made transparent, the light emitted from the adhesive surface of the light-emitting diode element can pass through the adhesive and reach the reflector, making it possible to collect light, and improving the light utilization efficiency.

[0004] Incidentally, the above-mentioned light-emitting diode reaches a high temperature of about 200° C. when emitting light, and therefore requires a silicone resin composition that exhibits the above-mentioned properties at such temperatures.

[0005] However, in the current situation, there is no known silicone resin composition that has such characteristics.That is, in Patent Document 1, a silicone resin composition is proposed that uses amorphous spherical silica as an inorganic filler, and combines a plurality of silicone resins with the inorganic filler to adjust the refractive index at the temperature of use, but the silicone resin composition is intended to be used at about 100°C, and cannot be used at high temperatures of around 200°C. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent Publication No. 2012-82314 Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made in consideration of such circumstances, and an object of the present invention is to provide a silicone resin composition that can be used at approximately 200°C, which is the temperature during operation of the light-emitting diode element, and that can exhibit high transparency at such operating temperature. [Means for solving the problem]

[0008] As a result of intensive research, the inventors have found that by blending an inorganic filler containing 90% or more by volume of magnesium fluoride particles and having a volume average particle size of 1 to 20 μm with a highly heat-resistant methyl-based silicone resin, it is possible to provide a silicone resin composition that can be used at approximately 200°C, which is the operating temperature of a light-emitting diode element, and that exhibits high transparency in this operating temperature range, thereby completing the present invention.

[0009] That is, the present invention is a silicone resin composition comprising a methyl-based silicone resin and an inorganic filler containing 90% by volume or more of magnesium fluoride particles and having a volume average particle size of 1 to 20 μm.

[0010] The amount of the inorganic filler to be blended is preferably 60 to 200 parts by volume relative to 100 parts by volume of the silicone resin, in order that the silicone resin composition exhibits higher thermal conductivity and strength when used as an adhesive.

[0011] Furthermore, the silicone resin composition is preferably used as a heat dissipation material, particularly as an adhesive between a light emitting element and a reflector of a light emitting diode. Effect of the Invention

[0012] The silicone resin composition of the present invention makes it possible to provide a silicone resin composition having high heat resistance and thermal conductivity, and high transparency at around 200°C. This silicone resin composition is suitable for use as a heat dissipation material that requires transparency. In particular, since the silicone resin composition has high transparency at around 200°C, which is the temperature during operation of a light-emitting diode, it can be used, for example, as an adhesive between a light-emitting element and a reflector of a light-emitting diode to increase the light-collecting efficiency of the light-emitting diode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The silicone resin composition of the present invention comprises a methyl-based silicone resin and an inorganic filler containing 90% by volume or more of magnesium fluoride particles and having a volume average particle size of 1 to 20 μm.

[0014] In the present invention, a methyl-based silicone resin having high heat resistance is used as the matrix material. Silicone resins are resins having siloxane bonds as the main chain and organic groups as side chains. The methyl-based silicone resin in the present invention is the above silicone resin in which the organic groups in the side chains are mainly composed of methyl groups.

[0015] The heat resistance of a silicone resin is strongly influenced by its structure, and if the organic groups in the side chains contain a large amount of functional groups other than methyl groups or are modified with other resins, the heat resistance decreases. In other words, by using a methyl-based silicone resin, a silicone resin composition with high heat resistance can be obtained.

[0016] As described above, in the methyl-based silicone resin of the present invention, the organic groups in the side chains are mainly methyl groups, and from the viewpoint of heat resistance, it is preferable that 90 mass % or more of the organic groups in the side chains are methyl groups, and more preferably 94 mass % or more of the organic groups in the side chains are methyl groups.

[0017] The methyl silicone resin of the present invention can be any known silicone resin without any restrictions, and several kinds of methyl silicone resins can be mixed and used. Commercially available methyl silicone resins include, for example, KER-2500 and KER-2700 manufactured by Shin-Etsu Chemical Co., Ltd., LUMISIL202 UV, LUMISIL203UV, LUMISIL205 UV, LUMISIL245 UV, and LUMISIL307 UV DAM manufactured by Asahi Kasei Wacker Silicone Co., Ltd., and SR2524, SR2650, SR2680, and SR2630 manufactured by Morikawa Silicone Co., Ltd.

[0018] The refractive index of a pure methyl silicone resin in which the side chains are not all modified with methyl groups is about 1.41. Here, the refractive index of a silicone resin is strongly affected by the organic group or modification of the side chain, so if a large amount of functional groups other than methyl groups are introduced into the organic group of the side chain or if it is modified with other resins, the heat resistance is usually significantly reduced and the refractive index is significantly different from 1.41. If the refractive index is within the range of 1.40 to 1.42, which is close to 1.41, it can be said that the side chain is mainly methyl groups and is not modified with a large amount of other resins, and has high heat resistance and the effect of the present invention can be obtained. Therefore, the refractive index of the methyl silicone resin of the present invention is 1.40 to 1.42, particularly 1.41.

[0019] In the present invention, the refractive index of the silicone resin is measured at 25° C. using an Abbe refractometer with a light source having a wavelength close to the D-line. Note that the refractive index of the silicone resin is measured in a paste state, and when the silicone resin composition is cured as described below, the refractive index of the silicone resin before curing is measured.

[0020] The inorganic filler of the present invention can be used that contains 90% or more by volume of magnesium fluoride particles. Conventionally used fillers such as silica and alumina have a high refractive index, and it was not possible to obtain a transparent resin composition by matching the refractive index of the matrix material made of methyl-based silicone resin with that of the filler. In contrast, the greatest feature of the present invention is that magnesium fluoride particles are used as the inorganic filler. Since magnesium fluoride has high thermal conductivity, it is possible to make the thermal conductivity of the silicone resin composition sufficiently high by using an inorganic filler containing magnesium fluoride. Furthermore, since magnesium fluoride has a refractive index of 1.38, when a heating element such as a light-emitting diode is operated and generates heat, the temperature reaches around 200°C, and when the methyl-based silicone resin composition expands and the refractive index decreases, the refractive index of the matrix and the filler almost matches, and the silicone resin composition becomes transparent.

[0021] The inorganic filler may contain less than 10% by volume of inorganic particles other than magnesium fluoride particles, but because high thermal conductivity is likely to be obtained in the silicone resin composition and high transparency at 200°C is likely to be obtained, the proportion of magnesium fluoride particles in the inorganic filler is preferably 95% by volume or more, more preferably 99% by volume or more, and particularly preferably 100% by volume.

[0022] The volume average particle diameter of the inorganic filler is 1 to 20 μm. By setting the volume average particle diameter of the inorganic filler to 1 to 20 μm, the fillability into the methyl-based silicone resin is improved, and the silicone resin composition can obtain sufficient thermal conductivity. The particle diameter is more preferably 1 to 15 μm, and most preferably 1 to 10 μm. The volume average particle diameter in the present invention is measured by a laser diffraction scattering method.

[0023] The shape of the inorganic filler is not particularly limited, but it is preferably spherical. By being spherical, the filling property into the methyl silicone resin is improved, and it is easy to give the silicone resin composition good operability and high thermal conductivity. In the present invention, spherical means that the circularity measured by image analysis of SEM images is 0.5 or more. It is more preferable that the circularity is 0.7 or more.

[0024] The refractive index of the inorganic filler of the present invention is preferably 1.37 to 1.39, and more preferably 1.38. By setting the refractive index of the inorganic filler within the above range, the transparency of the silicone resin composition at around 200°C can be improved.

[0025] When the inorganic filler contains inorganic particles other than magnesium fluoride particles, the refractive index of the inorganic particles is preferably 1.34 to 1.42, and more preferably 1.37 to 1.39. This is because when the refractive index of the inorganic particles is significantly different from that of magnesium fluoride, that is, significantly different from the refractive index of the methyl-based silicone resin at 200°C, the transparency of the silicone resin composition may decrease.

[0026] In the present invention, the refractive index of magnesium fluoride particles and other inorganic particles contained in the inorganic filler is measured at 25° C. for light of 632.8 nm. In the case of a particle that exhibits birefringence, such as magnesium fluoride, the arithmetic average of the two refractive index values ​​obtained by measurement is regarded as the refractive index of magnesium fluoride and other inorganic particles contained in the inorganic filler of the present invention. The refractive index is measured by the liquid immersion method.

[0027] The magnesium fluoride particles to be mixed in the inorganic filler of the present invention can be manufactured by a known method, but it is preferable to granulate the particles by atomization in the manufacturing process. In general atomization, a crucible has a hole sealed at the bottom and is equipped with a mechanism that can open the hole at any time, and the raw material (magnesium fluoride) held in the crucible is heated and melted to form a molten metal, and the molten metal is made to flow down from the open hole while a medium such as high-speed gas or water is blown onto the molten metal flowing down from the hole to make it fine, or the molten metal is brought into contact with a rotating disk and made to flow down from the hole by centrifugal force to make it fine. The finely granulated molten metal is sphericalized by surface tension before solidification, so that a powder with high sphericity can be easily obtained. Therefore, by granulation by atomization, it is easy to obtain magnesium fluoride particles having a volume average particle size of 1 to 20 μm and being spherical. The atomization can be performed using a known atomization processing device (atomizer). The conditions for the granulation process by atomization may be appropriately determined according to the target particle size, such as the molten metal temperature, the hole diameter of the crucible, the flow rate and speed of the sprayed gas or medium, and the rotation speed of the rotating disk.

[0028] The silicone resin composition of the present invention comprises the methyl silicone resin and the inorganic filler, and the amount of the inorganic filler is preferably 60 to 200 parts by volume, more preferably 100 to 200 parts by volume, and even more preferably 100 to 150 parts by volume, relative to 100 parts by volume of the methyl silicone resin.

[0029] The silicone resin composition of the present invention comprises a methyl silicone resin and an inorganic filler containing magnesium fluoride particles, and may also contain a curing catalyst as described below.

[0030] The method for producing the silicone resin composition of the present invention can use a known method. Specifically, the silicone resin composition can be produced by mixing the paste-like methyl silicone resin with an inorganic filler containing magnesium fluoride particles at a predetermined mixing ratio. The methyl silicone resin and the inorganic filler can be mixed in a mortar or the like, or can be mixed using a general device such as a gate mixer, a Banbury mixer, or a planetary mixer. In addition, the order of addition to the system during mixing can be any known order of addition without any particular restriction. For example, when the inorganic filler contains inorganic particles other than magnesium fluoride, magnesium fluoride and other inorganic particles can be mixed and then added to the methyl silicone resin, or magnesium fluoride and other inorganic particles can be added to the methyl silicone resin simultaneously or sequentially so as to be in a predetermined ratio.

[0031] It is also possible to mix the paste-like methyl silicone resin with magnesium fluoride and then cure it by a known method before use. When used as a heat dissipation material or adhesive as described below, it is usually cured before use. As a method of curing, for example, a method in which the paste-like methyl silicone resin is a condensation type silicone resin and has reactive functional groups capable of forming silanol bonds (e.g., silanol groups, alkoxysilyl groups), and these reactive functional groups are activated by heating or using a catalyst to react with each other and cure. In addition, a method in which the paste-like methyl silicone resin is an addition type silicone resin and has reactive functional groups capable of hydrosilyl reaction (e.g., hydroxysilyl groups and vinyl groups), and these reactive functional groups are heated or used with a catalyst to cure by hydrosilyl reaction can also be mentioned. Any known catalyst can be used without any particular limitation. Examples of catalysts for condensation type silicone resins include organotin compounds, organotitanium compounds, and quaternary ammonium salt compounds. Examples of catalysts for addition type silicone resins include platinum-based metal catalysts, palladium-based metal catalysts, rhodium-based metal catalysts, nickel-based metal catalysts, iron-based metal catalysts, and cobalt-based metal catalysts.

[0032] The silicone resin composition of the present invention is not particularly limited in its use, but is preferably used as a heat dissipation material in a portion where high heat dissipation and transparency are required. Specific examples include heat dissipation materials installed around optical elements such as light-emitting diode elements and laser elements, heat dissipation materials installed between semiconductor elements and substrates and requiring heat dissipation and transparency for alignment, and heat dissipation materials installed around windows of automobiles and buildings and requiring heat dissipation and transparency for improving aesthetics. Among them, it is preferably used as an adhesive between a light-emitting diode element and a reflector in a light-emitting diode. In a light-emitting diode, light emitted from the light-emitting diode composition is reflected and collected by the reflector, and light is collected. The light-emitting element is bonded and fixed to a part of the reflector by an adhesive. Since light is emitted from the light-emitting element in all directions, light is naturally emitted in the adhesive direction, but if the adhesive is opaque, the light emitted to the adhesive side is not collected at all. On the other hand, by using an adhesive that is transparent at the operating temperature of the light-emitting diode such as the silicone resin composition of the present invention, the light emitted to the adhesive side passes through the adhesive and reaches the reflector, where it is reflected and collected. The silicone resin composition of the present invention becomes highly transparent at around 200°C, the operating temperature of a light-emitting diode, and due to its high heat dissipation properties, can also function as a heat dissipation material for efficiently dissipating heat generated from a light-emitting diode element. Therefore, one of the preferred forms of use is as an adhesive between a light-emitting diode component and a reflector. EXAMPLES

[0033] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The abbreviations and titles shown in the examples are as follows. <Methyl silicone resin> S1: KER-2500 (Shin-Etsu Chemical Co., Ltd.), refractive index 1.41. <Inorganic filler> F1: spherical magnesium fluoride particles, volume average particle size 7.4 μm, refractive index 1.38. This inorganic filler was obtained according to the method for producing F1 described below. F2: Spherical alumina particles, CB-P05 (Showa Denko), volume average particle size 4.0 μm, refractive index 1.77. · F3: Spherical silica particles, Exelica SE8 (Tokuyama), volume average particle size 8.0 μm, refractive index 1.46.

[0034] Table 1 shows the composition of the silicone resin composition.

[0035] [Table 1]

[0036] The test methods are as follows:

[0037] (Production of inorganic filler F1) A gas atomizer (NEVA-GP2T type, manufactured by Nisshin Giken Co., Ltd.) was used to manufacture the inorganic filler F1. A carbon crucible was filled with lump magnesium fluoride and melted by high-frequency heating at 1350°C to obtain a molten metal. The molten magnesium fluoride was allowed to flow down from a hole in the bottom of the crucible while Ar gas was sprayed at a pressure of 1.0 MPa to pulverize the molten metal and powder it, obtaining spherical magnesium fluoride particles.

[0038] (Production of Silicone Resin Composition) The silicone resin and inorganic filler were weighed out in the prescribed amounts, mixed and defoamed using a planetary centrifugal mixer. The resulting slurry was filled into a mold measuring 50 mm x 50 mm x 0.3 mm thick, and heated at 100°C and 650 kPa / m 2 After pressing, the sample was placed in a 150°C oven for 5 hours to completely cure.

[0039] (Measurement of refractive index of silicone resin) The refractive index of the methyl silicone resin was measured in a thermostatic chamber at 25° C. using an Abbe refractometer (manufactured by Atago Co., Ltd.).

[0040] (Measurement of refractive index of inorganic filler) The refractive index of the inorganic filler used was measured by the liquid immersion method using an Abbe refractometer (manufactured by Atago Co., Ltd.). That is, in a thermostatic room at 25°C, 1 g of the inorganic filler was dispersed in 50 ml of methanol in a 100 ml sample bottle. While stirring this dispersion with a stirrer, 1-bromonaphthalene was added dropwise little by little, and the refractive index of the dispersion at the point when the dispersion became most transparent was measured, and the obtained value was taken as the refractive index of the inorganic filler.

[0041] (Measurement of the volume average particle size of inorganic fillers) The volume average particle size of the inorganic filler was measured using a laser diffraction scattering type particle size distribution analyzer (HORIBA, Ltd. LA-950). Sample preparation was performed by adding the inorganic filler to a solution using water as the dispersion medium and 0.1 wt% sodium hexametaphosphate (NaHMP) as the dispersant, and then subjecting it to ultrasonic treatment for 5 minutes.

[0042] (Measurement of Thermal Conductivity of Silicone Resin Composition) The thermal conductivity (W / m K) of a silicone resin composition is calculated by the thermal diffusivity (m 2 / sec) x density (kg / m 3 ) × specific heat (J / kg·K). The thermal diffusivity of the silicone resin composition was determined by temperature wave thermal analysis using a thermal diffusivity / thermal conductivity measuring device (Hitachi High-Tech: ai-Phase Mobile 2). The density of the silicone resin composition was determined by the Archimedes method, which calculates from the weight in air and the weight in water. The specific heat of the silicone resin composition was measured using a differential scanning calorimeter (Rigaku: Thermo Plus Evo DSC8230).

[0043] (Evaluation of Transparency of Silicone Resin Composition) A paper mount with printed characters was placed on a hot plate, and the silicone resin composition prepared to a thickness of 0.3 mm was placed on the plate. The hot plate was heated to 200°C and left to stand for 15 minutes, after which the visibility of the printed characters under the silicone resin composition was visually confirmed and evaluated according to the following criteria. ◯: The characters below the silicone resin composition are clearly visible. Δ: The characters below the silicone resin composition are barely visible. ×: The characters below the silicone resin composition are not visible.

[0044] <Example 1> 4.24g of silicone resin S1 and 19.02g of inorganic filler F1 were mixed and stirred according to the method for producing the silicone resin composition to obtain a silicone resin composition having 100 parts by volume of silicone resin and 150 parts by volume of inorganic filler. The thermal conductivity and transparency of the obtained silicone resin composition were measured. The evaluation results are shown in Table 2.

[0045] <Examples 2 and 3, Comparative Examples 1 to 4> Silicone resin compositions were produced in the same manner as in Example 1, except that the type and amount of inorganic filler were changed according to Table 1, and the thermal conductivity and transparency of the resulting silicone resin compositions were evaluated. The evaluation results are shown in Table 2.

[0046] [Table 2]

[0047] The evaluation results in Table 2 show that Examples 1 to 3, which contain an inorganic filler containing magnesium fluoride particles, exhibited thermal conductivity equal to or greater than that of Comparative Examples 1 to 5, which contain alumina or silica. This shows that the silicone resin composition containing an inorganic filler containing magnesium fluoride particles has sufficient thermal conductivity as a heat dissipation material.

[0048] Furthermore, Examples 1 to 3, in which an inorganic filler containing magnesium fluoride particles was blended, showed high transparency on a hot plate heated to 200° C. This means that the silicone resin composition has high transparency when heated to about 200° C., which is the operating temperature of a light-emitting diode.

[0049] From the above results, it can be said that a silicone resin composition consisting of a methyl-based silicone resin and an inorganic filler containing magnesium fluoride particles and having a volume average particle size of 1 to 20 μm has sufficient thermal conductivity as a heat dissipation material and has high transparency when heated to around 200°C, the operating temperature of a light-emitting diode, and is useful, for example, as an adhesive between the light-emitting diode element and reflector of a light-emitting diode.

Claims

1. A silicone resin composition comprising: a methyl-based silicone resin having a refractive index of 1.40 to 1.42 and in which 90 mass % or more of the organic groups in the side chains are methyl groups; and an inorganic filler containing 99 volume % or more magnesium fluoride particles and having a volume average particle size of 1 to 10 μm.

2. 2. The silicone resin composition according to claim 1, wherein the inorganic filler is mixed in an amount of 60 to 200 parts by volume per 100 parts by volume of the methyl-based silicone resin.

3. A heat dissipating material comprising the silicone resin composition according to claim 1 or 2.

Citation Information

Patent Citations

  • Thermally conductive silicone rubber composition

    JP1981163149A

  • Film having low refractive index

    JP1992202366A

  • Active energy ray-curable composition and laminated form

    JP2008001755A

  • Composition, cured coating film and article containing the same

    JP2010202857A

  • Transparent thermally conductive composition and transparent thermally conductive molding

    JP2012082314A